2004
DOI: 10.1111/j.1464-410x.2004.05157.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life and pain in chronic prostatitis/chronic pelvic pain syndrome: findings from the National Institutes of Health Chronic Prostatitis Cohort Study

Abstract: unique effects of age, partner status, urological symptoms, depressive symptoms and pain. RESULTSUrinary scores, depressive symptoms and pain intensity scores significantly predicted QoL for patients with CP/CPPS (higher CPSI QoL scores indicated more impairment; median 8.0, range 0-12). On average, for every 1-point increase in urinary scores, there was a corresponding increase in QoL score of 0.118 points ( P = 0.001); for every 1-point increase in pain intensity score, there was a corresponding increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 25 publications
(37 reference statements)
6
73
0
2
Order By: Relevance
“…20 Turner et al, 22 examining men in primary-care settings for QOL, reported that worse QOL was associated with greater pain and urinary symptoms and that pain was more robustly associated with worse QOL than were urinary symptoms. Recently, Tripp et al 23 also reported that pain intensity and urinary symptoms were independent predictors of QOL, with pain intensity the strongest predictor. The hallmark of CP/CPPS is its symptom complex, and, therefore, controlling the symptom profile is an integral part of managing this complex condition.…”
Section: Discussionmentioning
confidence: 98%
“…20 Turner et al, 22 examining men in primary-care settings for QOL, reported that worse QOL was associated with greater pain and urinary symptoms and that pain was more robustly associated with worse QOL than were urinary symptoms. Recently, Tripp et al 23 also reported that pain intensity and urinary symptoms were independent predictors of QOL, with pain intensity the strongest predictor. The hallmark of CP/CPPS is its symptom complex, and, therefore, controlling the symptom profile is an integral part of managing this complex condition.…”
Section: Discussionmentioning
confidence: 98%
“…The factors that contributed most to the reduced quality of life were pain intensity and quality of life subscale of the NIH-chronic prostatitis symptom index [36]. The general state of anxiety was higher in patients compared to their spouses and remained unchanged two years later [37].…”
Section: Psychosocial Factorsmentioning
confidence: 98%
“…In the mental QoL model, the catastrophizing mediation suggests that in men suffering from CP/CPPS, symptoms may become disabling through cognitive mechanisms, where catastrophizing creates an inability to disengage from negative pain ruminations. 27 This previously-identified style of negative CP/CPPS processing 5,7,10,12,14 can be modified, and reductions in catastrophizing have been shown to be associated with reductions in CP/CPPS symptoms. 28 This study also strongly indicated that illness-focused coping is an important target in improving patients' mental and physical QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The biopsychosocial experience of patients with CP/CPPS is critical for improved patient well-being, and a deeper understanding of the negative pain-QoL relationship is needed to advance patient management. 10 The urology and pain literature indicates that mood, cognitive appraisals (i.e., catastrophizing), and behavioural pain coping strategies are predictors for pain and QoL. Depression is elevated in CP/CPPS, 11 and catastrophizing is associated with greater pain in CP/CPPS, 12 as well as female chronic pelvic pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation